Amylodextrin produced by hydrochloric acid corrosion of raw rice as fat replacer - Escalante, L. V.; Merca, F. E.; Juliano, B. O. (2001)
The kinetics of preparation of amylodextrin (Lintner starch) was studied at 50 C as 35% rice-starch slurry in 1.0 M HCl. Based both on recovery of amylodextrin and amount of solubilized starch, under low and intermediate-high gelatinization temperature (GT), the amorphous fractions in two waxy and six non-waxy rice starches were corroded within 2 h of hydrolysis, after which the hydrolysis rate decreased. The change in slope was more pronounced in low-GT starches than in intermediate-high-GT starches. After 12-14 h, a third stage was noted, wherein an increase in hydrolysis rate was observed. This is possibly due to partial gelatinization of the amylodextrin and subsequent hydrolysis. Scale preparation from intermediate-high amylose-content rices for 18 h yielded 60-75% amylodextrin. Recovery of amylodextrin in both experiments was consistently higher from intermediate-high GT starch than from low-GT starch; amylose content had no effect. Differential scanning colorimetry revealed the temperature and enthalpy of gelatinization to be lower in the 18-h amylodextrin than in the native starch, but temperature was higher than 50 C. Mayonnaise prepared at 50 C (where aqueous gel of the 18-h hydrolysis amylodextrin of non-waxy flour and starch replaced 50% of the fat) was satisfactory and better than that obtained using raw rice starch.
Keywords: Rice; Hydrochloric acid